2013
DOI: 10.1007/s00592-013-0457-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in non-glycemic responses to improved insulin sensitivity by pioglitazone treatment in patients with type 2 diabetes

Abstract: Excess cortisol and GH induce insulin resistance, a central feature of type 2 diabetes (T2D). To study whether the insulin sensitizer pioglitazone affects basal cortisol levels and the GH-IGF-I axis in patients with T2D. Forty-eight patients with T2D (men/women = 28:20, age 61 ± 1 years, BMI 31 ± 0.6 kg/m(2)) were treated for 26 weeks with pioglitazone 30-45 mg daily in addition to their preexisting therapy. Insulin, proinsulin, HbA(1c), IGF-I, IGFBP-1, and basal cortisol were analyzed before and after treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 285 publications
0
8
0
Order By: Relevance
“…Hypoglycemia98 and fractures68 are more common in women than men on TZDs. We have found pioglitazone to increase basal serum cortisol in women but not in men, although the clinical significance of this is unclear 99. Women treated with rosiglitazone had higher mortality than men, while no differences were seen for other treatments eg, metformin 100…”
Section: Glucose-lowering Therapymentioning
confidence: 83%
“…Hypoglycemia98 and fractures68 are more common in women than men on TZDs. We have found pioglitazone to increase basal serum cortisol in women but not in men, although the clinical significance of this is unclear 99. Women treated with rosiglitazone had higher mortality than men, while no differences were seen for other treatments eg, metformin 100…”
Section: Glucose-lowering Therapymentioning
confidence: 83%
“…showed that pioglitazone improves insulin sensitivity by inhibiting IGFBP1 synthesis thereby increasing free IGF1 and the change in IGFBP1 in subjects with established type II diabetes begun on pioglitazone correlates with a change in adiponectin (Arnetz et al 2014). IGFBP1 was shown to increase beta cell regeneration by promoting alpha to beta cell transdifferentiation in mouse and human islets (Lu et al 2016).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%
“…A Diabetes Outcome Progression Trial (ADOPT) and Rosiglitazone Evaluated for Cardiovascular Outcomes and Regulation of Glycemia in Diabetes (RECORD) reported that obese females had a greater HbA1c reduction with TZDs than that with sulfonylureas (p < 0.001) [29] . Additionally, triglycerides decreased signi cantly in women but not in men with pioglitazone treatment (p = 0.015) [30] . Our previous study showed that after pioglitazone treatment, women experienced a greater drop in blood glucose and insulin (Supplemental data 1).…”
Section: Discussionmentioning
confidence: 98%